Why Process Is (Almost) Everything (Existential Analysis: Journal of the Society for Existential Analysis, 2016)
An exploration of process in contemporary existential therapy drawing from the realist novel, phenomenology and recent developments in affect theory and neurodiversity.
Keywords: Process; affect; realist literature; neurodiversity.